Itaconate: an emerging determinant of inflammation in activated macrophages. Issue 2 (11th December 2018) - Yu, Xiao‐Hua; Zhang, Da‐Wei; Zheng, Xi‐Long; Tang, Chao‐Ke
Abstract: Macrophages play a central role in innate immunity as the first line of defense against pathogen infection. Upon exposure to inflammatory stimuli, macrophages rapidly respond and subsequently undergo metabolic reprogramming to substantially produce cellular metabolites such as itaconate. As a derivate of the tricarboxylic acid cycle, itaconate is derived from the decarboxylation of cis ‐aconitate mediated by immunoresponsive gene 1 in the mitochondrial matrix. It is well known that itaconate has a direct antimicrobial effect by inhibiting isocitrate lyase. Strikingly, two recent studies published in Nature showed that itaconate markedly decreases the production of proinflammatory mediators in lipopolysaccharide‐treated macrophages and ameliorates sepsis and psoriasis in animal models, revealing a novel biological action of itaconate beyond its regular roles in antimicrobial defense. The mechanism for this anti‐inflammatory effect has been proposed to involve the inhibition of succinate dehydrogenase, blockade of IκBζ translation and activation of Nrf2. These intriguing discoveries provide a new explanation for how macrophages are switched from a pro‐ to an anti‐inflammatory state to limit the damage and facilitate tissue repair under proinflammatory conditions. Thus, the emerging effect of itaconate as a crucial determinant of macrophage inflammation has important implications in further understanding cellular immunometabolism and developing future therapeutics for the treatment of inflammatory diseases. In this review, we focus on the roles of itaconate in controlling the inflammatory response during macrophage activation, providing a rationale for future investigation and therapeutic intervention. Abstract : Itaconate protects against macrophage inflammation by inhibiting succinate dehydrogenase (SDH), activating Nrf2 and blocking IκBζ translation. Targeting itaconate could be an important new strategy for the treatment of inflammatory diseases.